WITH REGARD TO THE QUESTION ABOUT THE USE OF ARTIFICIAL BARRIERS IN AREAS WITH MAN-MADE INFLUENCE - Tsurik, Tatyana; Kolomanich, Anastasia (Journal of Applied Engineering Science, 2021)
One of the ways to improve the environmental situation in various regions of the world has become the improvement of technologies for protection against hazardous pollution in soil, atmosphere, groundwater. The article is devoted to the analysis of the conceptual proposal within the framework of participation in the competition “Students reinventing cities. The promising methods of elimination and localization of environmental pollution using geochemical barriers are outlined. Examples of natural and artificial geochemical barriers are considered. Attention is drawn to the possibility of using anti-filtration screens as artificial barriers in areas with passive technogenic impact. The potential of using artificial barriers for the safe cultivation of plant crops at the former Payatas controlled waste disposal facility in Quezon City, Philippines is being identified. The importance of creating green spaces in the territory with limited opportunities for economic use is justified.